Dilthey and psychology - Molina, Javier (2006)
German romanticism is considered one of the sources that influenced the thought of Wilhelm Dilthey, in the way he conceived his theory of knowledge, his theory of science and his view of psychology. Novalis, a german romanticist, was one of the influences of Dilthey’s thought. This article examines how the concepts such as “genius”, “sciences of the spirit”, “real psychology”, and the role of individuality in the study of human will, based on the psychological theories of the time of Novalis, determine the way Dilthey was influenced by Novalis. A research conducted by Dilthey in 1894 shows Dilthey’s conception of scientific methodology, particularly his views of psychology, which stands in opposition to the growing experimental psychology and its constructive-explanatory methodology.